Stroke risk following bee and wasp stings: a systematic review of ischemic and hemorrhagic events - Vasconez-Gonzalez, Jorge; Izquierdo-Condoy, Juan S.; Delgado-Moreira, Karen; Noboa-Lasso, María de Lourdes; Gamez-Rivera, Esteban; Salazar-Santoliva, Camila; Belén Lopez-Molina, María; Ortiz-Prado, Esteban (Frontiers in Toxicology, 2025)
BackgroundEach year, approximately 100 million cases of bee and wasp stings are re-ported globally, with the majority resulting in mild reactions. However, in rarer instances, these stings can lead to severe and potentially fatal outcomes, including ischemic or hemorrhagic cerebral events. This article aims to synthesize and analyze the current evidence on the association between bee and wasp stings and the occurrence of ischemic and hemorrhagic strokes.MethodologyA systematic review was conducted in accordance with PRISMA guidelines. Searches were performed in PubMed, Scopus, and Scielo databases, including studies published in English and Spanish without time restrictions. Studies that met the inclusion criteria, specifically focusing on “bee sting” or “wasp sting” and “stroke” or “cerebrovascular disease” in humans, were included.ResultsOut of the 83 articles initially identified, 28 met the inclusion criteria and were included in this systematic review, documenting a total of 29 cases of stroke associated with bee or wasp stings. The distribution of cases was nearly equal between bee and wasp stings. Ischemic stroke emerged as the most commonly reported type, with clinical manifestations primarily affecting the nervous system. Common symptoms included hemiparesis or hemiplegia, hypertension, dysarthria or aphasia, and loss of consciousness or syncope. This pattern underscores the significant neurological and systemic impact of envenomation, which, while rare, can lead to severe and potentially life-threatening complications.ConclusionWhile cerebrovascular events like ischemic and hemorrhagic strokes following bee or wasp stings are rare, the risk is significant and can be life-changing. The impact of a stroke extends beyond immediate symptoms, affecting long-term quality of life. Therefore, it is crucial that healthcare facilities establish protocols to recognize and manage these rare but severe complications. Further research is needed to better understand and mitigate this risk.